Paint it black: Chronic whiting event degrades bottom communities in a Mediterranean coastal lagoon - Víctor Orenes-Salazar; Adrián Guerrero-Gómez; Antonio Zamora-López; Antonio Ortolano; Marijn Oosterbaan; Antonio A. Herrero-Reyes; Patricio López-Martínez de la Plaza; Eugenio Fraile-Nuez; Mar Torralva; Juan Manuel Ruíz; Lázaro Marín-Guirao (Marine Pollution Bulletin, 2026)

Fish functional responses to eutrophication and mass mortality events in a Mediterranean coastal lagoon - Antonio Zamora-López; Adrián Guerrero-Gómez; Mar Torralva; José Manuel Zamora-Marín; Antonio Andrés Herrero-Reyes; Pedro Miguel Guerreiro; Francisco José Oliva-Paterna (Marine Pollution Bulletin, 2026)

First record of winter pregnant males of two pipefish species in a Mediterranean coastal lagoon - Adrián Guerrero‐Gómez; Antonio Zamora‐López; Antonio Andrés Herrero‐Reyes; Francisco J. Oliva‐Paterna; Jorge Madrid‐Ruiz; Víctor M. Álvarez‐Navarro; Rocío Peñalver; Mar Torralva (Journal of Fish Biology, 2025)
Syngnathus abaster Risso, 1827 and Syngnathus typhle L., 1758 are key components of fish assemblages in European transitional waters, with well‐documented reproductive cycles typically occurring from spring to autumn. However, recent warming trends in the western Mediterranean has raised questions about potential shifts in their breeding phenology. In January 2025, three pregnant S. abaster males and one S. typhle male were detected in the Mar Menor Coastal lagoon (western Mediterranean), representing the first recorded winter breeding event for both species. The size structure of S. abaster in winter 2025 also contrasted with colder winters, further supporting this interpretation. These findings may reflect a response to recent thermal anomalies and highlight the phenological plasticity of these species. To our knowledge, this is the first indication of potential phenological shifts in syngnathids from transitional waters, with implications for understanding how climate change may influence their reproductive dynamics.

Eutrophication-induced shifts in fish assemblages from a Mediterranean coastal lagoon - Antonio Zamora-López; Adrián Guerrero-Gómez; Mar Torralva; José Manuel Zamora-Marín; Francisco José Oliva-Paterna (Science of The Total Environment, 2025)

Spatiotemporal dynamics and species-habitat relationships in syngnathid assemblages from a coastal lagoon under eutrophication stress - Adrián Guerrero-Gómez; Antonio Zamora-López; José Manuel Zamora-Marín; Francisco José Oliva-Paterna; Mar Torralva (Marine Environmental Research, 2025)

To preserve, monitor or eradicate: Covert rewilding as an emerging conservation trilemma for wildlife managers - José Manuel Zamora-Marín; José A. Sánchez-Zapata; Adrián Guerrero-Gómez; Antonio Zamora-López; Mar Torralva; Francisco J. Oliva-Paterna; David Sánchez-Fernández (Biological Conservation, 2025)

Population dynamics of resident fish in a coastal lagoon under eutrophication-mediated habitat changes - ADRIÁN GUERRERO-GÓMEZ; ANTONIO ZAMORA-LÓPEZ; MAR TORRALVA; JOSÉ MANUEL ZAMORA-MARÍN; ANTONIO GUILLÉN-BELTRÁN; FRANCISCO OLIVA-PATERNA J. (Mediterranean Marine Science, 2024)
Coastal lagoons, as transitional ecosystems, are crucial for providing ecosystem services and preserving fish communities, yet they face increasing pressures from anthropogenic activities. The Mar Menor coastal lagoon in the western Mediterranean exemplifies this challenge, as it suffers from severe eutrophication driven by agricultural and urban influences. In this study, we assess changes in the population dynamics of three resident fish species (Apricaphanius iberus, Pomatoschistus marmoratus, and Syngnathus abaster) in the context of human-induced impacts in the Mar Menor. Using long-term monitoring data (the reference period of 2002-2004 vs. the eutrophication period of 2015-2019), we analyze temporal variations in their population dynamics and their relationships with eutrophication-mediated structural changes in shallow waters. Our results suggest that these resident species, which are closely associated with shallow areas, show population dynamics that reflect habitat alterations, underscoring their potential as indicators of eutrophication impacts. This study enhances our understanding of the dynamics within transitional ecosystems and provides a basis for integrated management strategies aimed at promoting effective fish conservation.

From small waterbodies to large multi-service providers: Assessing their ecological multifunctionality for terrestrial birds in Mediterranean agroecosystems - José M. Zamora-Marín; Antonio Zamora-López; Francisco J. Oliva-Paterna; Mar Torralva; María Mar Sánchez-Montoya; José F. Calvo (Agriculture, Ecosystems & Environment, 2024)

A review and meta-analysis of the environmental biology of bleak Alburnus alburnus in its native and introduced ranges, with reflections on its invasiveness - Dani Latorre; Guillem Masó; Carlos Cano-Barbacil; José M. Zamora-Marin; David Almeida; Lorenzo Vilizzi; J. Robert Britton; Alejandra Cruz; Carlos Fernández-Delgado; Anni G. González-Rojas; Rafael Miranda; Francesc Rubio-Gracia; et al. (Reviews in Fish Biology and Fisheries, 2023)
The bleak Alburnus alburnus is a medium body-size leuciscid fish that is naturally distributed across central European and western Asian fresh waters. However, during the last two decades A. alburnus has been widely introduced elsewhere in Europe and in northern Africa, mostly as a forage species for game fishes. Given its relatively recent history of invasion in non-native Eurasian waters, where it can become highly abundant, A. alburnus poses a serious risk to native communities where introduced. This study provides a review and meta-analysis of the biological traits of A. alburnus coupled with insights into its invasiveness. In its native range, A. alburnus has a moderate lifespan, inhabiting lakes or still waters in medium-to-large rivers, where it feeds mainly on zooplankton. However, non-native A. alburnus populations display high phenotypic plasticity in their biological attributes. Thus, growth, reproductive and/or dietary traits have adapted to local environmental conditions, with the species also invading lotic (stream) ecosystems. Feeding changes to benthic invertebrates, plant material and detritus when zooplankton is scarce. Such plasticity, including broad physiological tolerance, is likely to facilitate the species' adaptation and invasion of new habitats in the near future.

Shallow waters as critical habitats for fish assemblages under eutrophication-mediated events in a coastal lagoon - Antonio Zamora-López; Adrián Guerrero-Gómez; Mar Torralva; José Manuel Zamora-Marín; Antonio Guillén-Beltrán; Francisco José Oliva-Paterna (Estuarine, Coastal and Shelf Science, 2023)

Corrigendum to ‘A horizon scan exercise for aquatic invasive alien species in Iberian inland waters’ Sci. Total Environ.869 (2023) 161798 - Francisco J. Oficialdegui; José M. Zamora-Marín; Simone Guareschi; Pedro M. Anastácio; Pablo García-Murillo; Filipe Ribeiro; Rafael Miranda; Fernando Cobo; Belinda Gallardo; Emili García-Berthou; Dani Boix; Andrés Arias; et al. (Science of The Total Environment, 2023)

A horizon scan exercise for aquatic invasive alien species in Iberian inland waters - Francisco J. Oficialdegui; José M. Zamora-Marín; Simone Guareschi; Pedro M. Anastácio; Pablo García-Murillo; Filipe Ribeiro; Rafael Miranda; Fernando Cobo; Belinda Gallardo; Emili García-Berthou; Dani Boix; Andrés Arias; et al. (Science of The Total Environment, 2023)

Effective monitoring of freshwater fish - Johannes Radinger; J. Robert Britton; Stephanie M. Carlson; Anne E. Magurran; Juan Diego Alcaraz‐Hernández; Ana Almodóvar; Lluís Benejam; Carlos Fernández‐Delgado; Graciela G. Nicola; Francisco J. Oliva‐Paterna; Mar Torralva; Emili García‐Berthou (Fish and Fisheries, 2019)
Freshwater ecosystems constitute only a small fraction of the planet's water resources, yet support much of its diversity, with freshwater fish accounting for more species than birds, mammals, amphibians or reptiles. Fresh waters are, however, particularly vulnerable to anthropogenic impacts, including habitat loss, climate and land use change, pollution and biological invasions. This environmental degradation, combined with unprecedented rates of biodiversity change, highlights the importance of robust and replicable programmes to monitor freshwater fish. Such monitoring programmes can have diverse aims, including confirming the presence of a single species (e.g., early detection of alien species), tracking changes in the abundance of threatened species, or documenting long‐term temporal changes in entire communities. Irrespective of their motivation, monitoring programmes are only fit for purpose if they have clearly articulated aims and collect data that can meet those aims. This review, therefore, highlights the importance of identifying the key aims in monitoring programmes and outlines the different methods of sampling freshwater fish that can be used to meet these aims. We emphasize that investigators must address issues around sampling design, statistical power, species’ detectability, taxonomy and ethics in their monitoring programmes. Additionally, programmes must ensure that high‐quality monitoring data are properly curated and deposited in repositories that will endure. Through fostering improved practice in freshwater fish monitoring, this review aims to help programmes improve understanding of the processes that shape the Earth's freshwater ecosystems and help protect these systems in face of rapid environmental change.

Growth plasticity of the southern Iberian barbel along longitudinal gradients in a highly regulated Mediterranean basin. - Sánchez-Pérez Ana; Oliva-Paterna Francisco José; Verdiell-Cubedo David; Ruiz-Navarro Ana; Torralva Mar (Frontiers in Marine Science, 2015)

Comparative population genetic structure and demographic patterns of two killifish species (Aphanius baeticus and Aphanius iberus) at the Iberian Peninsula - Gonzalez Elena; Pedraza Carlos; Cunha Carina; Oliva-Paterna Francisco; Torralva Mar; Doadrio Ignacio (Frontiers in Marine Science, 2015)

LIFE Segura-Riverlink as a green infrastructure approach to recover the longitudinal connectivity: preliminary data of the fish-based assessment. - Oliva-Paterna Francisco José; Sánchez-Pérez Ana; Amat-Trigo Fátima; Zamora-Marín José Manuel; Verdiell-Cubedo David; Ruiz-Navarro Ana; Sanz-Ronda Francisco Javier; Lafuente Eduardo; Torralva Mar (Frontiers in Marine Science, 2015)

Population size structure of non-native fishes along longitudinal gradients in a highly regulated Mediterranean basin. - Amat-Trigo Fátima; Torralva-Forero Mar; Verdiell-Cubedo David; Ruiz-Navarro Ana; Oliva-Paterna Francisco José (Frontiers in Marine Science, 2015)

Non-native freshwater fishes in the Iberian Southeast: black list and potential impacts - Amat-Trigo Fátima; Torralva-Forero Mar; Oliva-Paterna Francisco José (Frontiers in Marine Science, 2015)

Assessing the nursery role for marine fish species in a hypersaline coastal lagoon (Mar Menor, Mediterranean Sea) - David Verdiell-Cubedo; Francisco J. Oliva-Paterna; Ana Ruiz-Navarro; Mar Torralva (Marine Biology Research, 2013)

Effects of Shoreline Urban Modification on Habitat Structure and Fish Community in Littoral Areas of a Mediterranean Coastal Lagoon (Mar Menor, Spain) - David Verdiell-Cubedo; Mar Torralva; Asunción Andreu-Soler; Francisco J. Oliva-Paterna (Wetlands, 2012)

Behavioral responses of the Iberian waterfrog, Pelophylax perezi (Seoane, 1885), to three nitrogenous compounds in laboratory conditions - Andrés Egea-Serrano; Miguel Tejedo; Mar Torralva (Ecotoxicology, 2011)

Threatened fishes of the world: Valencia hispanica (Valenciennes, 1846) (Valenciidae) - Francisco J. Oliva-Paterna; Nuno Caiola; Mar Torralva (Environmental Biology of Fishes, 2009)

Analysis of the Avoidance of Nitrogen Fertilizers in the Water Column by Juvenile Iberian Water Frog, Pelophylax perezi (Seoane, 1885), in Laboratory Conditions - Andrés Egea-Serrano; Miguel Tejedo; Mar Torralva (Bulletin of Environmental Contamination and Toxicology, 2008)

Breeding Habitat Selection of Salamandra salamandra (Linnaeus, 1758) in the Most Arid Zone of its European Distribution Range: Application to Conservation Management - Andrés Egea-Serrano; Francisco J. Oliva-Paterna; Mar Torralva (Hydrobiologia, 2006)

Threatened Fishes of the World: Aphanius iberus (Cuvier & Valenciennes, 1846) (Cyprinodontidae) - Francisco J. Oliva-Paterna; Mar Torralva; Carlos Fernández-Delgado (Environmental Biology of Fishes, 2006)

Habitat quality affects the condition of Barbus sclateri in Mediterranean semi-arid streams - Francisco J. Oliva-Paterna; Pedro A. Miñnano; Mar Torralva (Environmental Biology of Fishes, 2003)

Effect of river regulation on the life‐history patterns of Barbus sclateri in the Segura river basin (south‐east Spain) - M. Del Mar Torralva; M. Angeles Puig; C. Fernández‐delgado (Journal of Fish Biology, 1997)
The age structure, growth and reproduction of Barbus sclateri in a non‐regulated section of the Segura River were similar to previously studied populations of undisturbed areas. Differences in the duration of the growth period or the reproductive cycle are considered evidence of the plasticity of the species as it adapts to different latitudes and local habitat characteristics. However, this population differed from one in a section with artificial water flow regulation. The non‐regulated river population had a greater number of age groups, displayed a regular condition cycle, reached maturity earlier at lower ages and lengths and showed greater fecundity than the regulated river population. The mean lengths at age were longer in the regulated river population, possibly owing to the longer river section studied and/or to selective mortality of smaller specimens within a particular age group from the high water velocity when sluices are opened.